Safety surveillance and challenges in accelerated COVID-19 vaccine development - Abimbola Cole; Peggy Webster; Denny Van Liew; Maribel Salas; Omar Aimer; Marina A. Malikova (SAGE Publishing, 2022)
The COVID-19 pandemic, caused by a novel type of coronavirus, continues to infect people, increasing morbidity and mortality across the globe. Measures to slow the transmission of the virus have had limited impact, and people, businesses, and economies have suffered. The disease has disproportionally impacted elderly and individuals with certain pre-existing conditions and has highlighted health and social inequities in some racial and ethnic minority groups. The majority of those who contract the disease recover completely, but some experience long-lasting complications. Vaccines have the potential to end the pandemic, and through the intense collaboration of scientists in government and private sectors, more than 200 COVID-19 candidate vaccines have been or are being developed, using known platforms and previous experiences with severe acute respiratory syndrome (SARS), at unprecedented speed. The expectations for vaccine safety and quality in the setting of accelerated development are the same as during non-emergency times; however, challenges inherent with the circumstances of the pandemic situation provide opportunities to improve clinical trial conduct and strengthen pharmacovigilance systems. We have reviewed and analyzed existing PV guidelines and recommendations throughout the lifecycle of vaccine development with a focus on developing a global/worldwide effort for post-marketing vaccine safety surveillance. Plain Language Summary The Important Role of Pharmacovigilance in Accelerated COVID-19 Vaccine Development This is an extensive review that intends to address important aspects of COVID-19 vaccines' accelerated development and safety surveillance. It is focused on regulatory requirements for long-term safety monitoring, practical applications, and current global efforts in developing robust pharmacovigilance systems for post-authorization surveillance. Notably, different perspectives of authors from industry, academic institutions, and contract research organizations involved in drug safety were incorporated to reflect on various regulatory requirements and new developments in vaccine safety. All co-authors are current members of International Society of Pharmacovigilance (ISoP).